Nafs Mutmainah sebagai Dasar dalam Menciptakan Kesejahteraan Spiritual - Afandi, Nur Kholik (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Spiritual well-being is the ability to develop harmonious relationships with himself, others, the universe (environment), and transcendental aspects. In the Islamic perspective, these values are reflected in the way of view, attitudes and behaviors called morals (akhlak). The implementation of moral values in everyday life, will form a person who has personal piety, social, environmental, ritual and spiritual. This multidimensional piety arises because of the encouragement of the person who has nafs mutaminnah, namely a calm soul, sincerity, and based on the values of faith.